2022
DOI: 10.1101/2022.05.11.22274903
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A rapid review of the effectiveness of interventions and innovations relevant to the Welsh NHS context to support recruitment and retention of clinical staff

Abstract: The National Health Service (NHS) is experiencing an acute workforce shortage in every discipline, at a time when waiting times are at a record high and there is a growing backlog resulting from the COVID-19 pandemic. This Rapid Review aimed to explore the effectiveness of interventions or innovations relevant to the Welsh NHS context to support recruitment and retention of clinical staff. The review is based on the findings of existing reviews supplemented by a more in-depth evaluation of included primary stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…▪ Our previous work regarding recruitment and retention of NHS staff did not retrieve any research related to paramedics, indicating a clear gap in research (Edwards et al 2022b, Edwards et al 2022a).…”
Section: Areas Of Uncertaintymentioning
confidence: 95%
“…▪ Our previous work regarding recruitment and retention of NHS staff did not retrieve any research related to paramedics, indicating a clear gap in research (Edwards et al 2022b, Edwards et al 2022a).…”
Section: Areas Of Uncertaintymentioning
confidence: 95%
“…If multiple systematic reviews were identi ed, then a review of existing reviews was considered for the subsequent phase Rapid Review. For example, in our review of innovations to support patients on elective surgical waiting lists (RR_30) [21] and our review of interventions to recruitment and retain clinical staff (RR_28) [22].…”
Section: Output From Phase Imentioning
confidence: 99%
“…This enabled wider sharing and the collection of metrics. For example, the abstract of a rapid review on the effectiveness of interventions and innovations relevant to the Welsh NHS context to support recruitment and retention of clinical staff, [32] was viewed 671 times, and the pdf was downloaded 181 times in the first 3 months. While some evidence was not directly included in Welsh Government papers, feedback from stakeholders indicated that information confirmed their knowledge and was useful:…”
Section: Group Public Contributors Who Support Research Activities At...mentioning
confidence: 99%